Electroacupuncture treatment ameliorates metabolic disorders in obese ZDF rats by regulating liver energy metabolism and gut microbiota - Ding, Lei; Teng, Rufeng; Zhu, Yifei; Liu, Fengming; Wu, Lili; Qin, Lingling; Wu, Xi; Liu, Tonghua (Frontiers in Endocrinology, 2023)
Metabolic disorders represent a major therapeutic challenge to public health worldwide due to their dramatically increasing prevalence. Acupuncture is widely used as adjuvant therapy for multiple metabolic diseases. However, detailed biological interpretation of the acupuncture stimulations is still limited. The gut and the liver are intrinsically connected and related to metabolic function. Microbial metabolites might affect the gut-liver axis through multiple mechanisms. Liver metabolomics and 16S rRNA sequencing were used to explore the specific mechanism of electroacupuncture in treating ZDF rats in this study. Electroacupuncture effectively improved glycolipid metabolism disorders in ZDF rats. Histopathology confirmed that electroacupuncture improved diffuse hepatic steatosis and hepatocyte vacuolation and promoted glycogen accumulation in the liver. The treatment significantly improved microbial diversity and richness and upregulated beneficial bacteria that maintain intestinal epithelial homeostasis and decreased bacteria with detrimental metabolic features on host metabolism. Liver metabolomics shows that the main effects of electroacupuncture include reducing the carbon flow and intermediate products in the TCA cycle, regulating the metabolism of various amino acids, and inhibiting hepatic glucose output and de novo lipogenesis. The gut-liver axis correlation analysis showed strong correlation between the gut microbiota and liver metabolites, especially allantoin and Adlercreutzia. Electroacupuncture treatment can improve abnormal energy metabolism by reducing oxidative stress, ectopic fat deposition, and altering metabolic fluxes. Our results will help us to further understand the specific mechanism of electroacupuncture in the treatment of metabolic diseases.